1999
DOI: 10.1007/s002210050721
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the depression of H-reflexes following previous activation in upper and lower limb muscles in human subjects

Abstract: When conditioning-testing (C-T) stimuli are applied to Ia afferents to elicit H-reflexes, the test reflex is abolished immediately following the conditioning reflex. As the C-T interval is increased, the test response slowly begins to recover, taking several hundred milliseconds to attain control values. The time course of this recovery is known as the H-reflex recovery curve. H-reflex recovery curves were compared using surface EMG and single motor unit activities in lower limb soleus and upper limb flexor ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
1
37
1
Order By: Relevance
“…This is intuitively reasonable because lesser depression of Ia synaptic effects on low-threshold motoneurons would render those motoneurons more responsive to the same Ia volley. Given the relatively small test reflex in this study, this would also explain the lower rate dependence seen here than in other studies of low-frequency depression of the soleus H reflex (Burke et al 1989;Calancie et al 1993;Cook 1968;Floeter and Kohn 1997;Hoehler and Buerger 1983;Hoehler et al 1981;Ishikawa et al 1966;Meunier et al 2007;Rossi-Durand et al 1999;Rothwell et al 1986;Schindler-Ivens and Shields 2000;Van Boxtel 1986).…”
Section: Hd Studied With Threshold Trackingcontrasting
confidence: 50%
See 2 more Smart Citations
“…This is intuitively reasonable because lesser depression of Ia synaptic effects on low-threshold motoneurons would render those motoneurons more responsive to the same Ia volley. Given the relatively small test reflex in this study, this would also explain the lower rate dependence seen here than in other studies of low-frequency depression of the soleus H reflex (Burke et al 1989;Calancie et al 1993;Cook 1968;Floeter and Kohn 1997;Hoehler and Buerger 1983;Hoehler et al 1981;Ishikawa et al 1966;Meunier et al 2007;Rossi-Durand et al 1999;Rothwell et al 1986;Schindler-Ivens and Shields 2000;Van Boxtel 1986).…”
Section: Hd Studied With Threshold Trackingcontrasting
confidence: 50%
“…It would be expected that there would be differences in the extent of HD operating on the afferent projections to low-threshold and high-threshold mo-toneurons. Previous studies present evidence that small reflexes are more susceptible to low-frequency depression than large reflexes (Cook 1968;Field-Fote et al 2006;Floeter and Kohn 1997;Lloyd and Wilson 1957;Rossi-Durand et al 1999;Van Boxtel 1986), in keeping with the greater susceptibility of small reflexes to facilitation or inhibition (Crone et al 1990;Meinck 1980). However, a number of factors determine this susceptibility, and it cannot be construed as evidence that HD is necessarily greater on the afferent projection to low-threshold motoneurons.…”
Section: Hd Studied With Threshold Trackingmentioning
confidence: 85%
See 1 more Smart Citation
“…It has been shown that the amplitude of H-reflex diminishes when stimuli are closely spaced in time. On the upper limb, the recovery between two stimulations is achieved in Ͻ1 s (Rossi-Durand et al 1999). In our experiment, the ISI could fluctuate according to the time necessary for subjects to initiate the task or follow the indicated path.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…The ISI was randomized from 4 to 70 ms in a uniform distribution. The interval between each double-stimulus sequence was set to 1 s, given that the H-reflex amplitude can fully recover within 200 ms (Rossi-Durand et al 1999). A total of 800 -1,000 double stimulations were applied.…”
Section: Experimental Data Collection and Analysismentioning
confidence: 99%